1999
DOI: 10.1055/s-2007-1013146
|View full text |Cite
|
Sign up to set email alerts
|

Management of Symptomatic Hypertrophic Obstructive Cardiomyopathy - Long-Term Results after Surgical Therapy

Abstract: We have examined the outcome of a large series of patients treated surgically for HOCM since 1963. The majority of patients were in NYHA class III and came to surgery after long-term medical, but finally insufficient, management. The perioperative risk could be reduced considerably during recent years, despite the advanced cardiomyopathy status. The long-term postoperative observation of the patients demonstrated an unexpectedly continuing good outcome. Therefore these results may serve as a standard for asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0
13

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 22 publications
0
49
0
13
Order By: Relevance
“…[5][6][7][8][9][10][11][12] In fact, it has been suggested that surgical myectomy alters the natural course of HCM and most patients have a lifespan similar to an age-matched population. 5 However, there are only a few reports of outcomes in patients that also underwent concomitant mitral valve surgery or CABG, 11,12 because most of these studies reported outcomes of only those patients that underwent isolated surgical myectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12] In fact, it has been suggested that surgical myectomy alters the natural course of HCM and most patients have a lifespan similar to an age-matched population. 5 However, there are only a few reports of outcomes in patients that also underwent concomitant mitral valve surgery or CABG, 11,12 because most of these studies reported outcomes of only those patients that underwent isolated surgical myectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Based on previous reports, up to 70% HCM patients have demonstrable left ventricular outflow tract (LVOT) obstruction, 4 with a significant proportion requiring a surgical myectomy (with or without concomitant mitral valve procedures) to relieve intractable symptoms despite maximal medical therapy, with excellent long-term outcomes. [5][6][7][8][9][10][11][12] It has also been previously suggested that surgical myectomy alters the natural course of HCM patients with severe symptomatic LVOT obstruction, and most patients have a lifespan similar to an age-matched population. 5 However, we frequently encounter patients who require more than an isolated myectomy to optimally relieve LVOT obstruction (ie, concomitant mitral valve repair/replacement).…”
mentioning
confidence: 99%
“…[1][2][3][4] The therapy most widely applied is surgical myectomy by removing a small amount of muscle from the basal interventricular septum. [5][6][7][8][9] Surgery substantially reduces the subaortic outflow gradient in Ͼ90% of patients and results in persistent symptomatic improvement in Ϸ70% to 90%. [1][2]4,[7][8][9][10] In recent years, transcoronary ablation of septal hypertrophy (TASH) by selective transcatheter septal branch injection of ethanol has been shown to substantially reduce outflow obstruction in 80% to 90% and symptoms in 84% to 90% of patients.…”
mentioning
confidence: 99%
“…[5][6][7][8][9] Surgery substantially reduces the subaortic outflow gradient in Ͼ90% of patients and results in persistent symptomatic improvement in Ϸ70% to 90%. [1][2]4,[7][8][9][10] In recent years, transcoronary ablation of septal hypertrophy (TASH) by selective transcatheter septal branch injection of ethanol has been shown to substantially reduce outflow obstruction in 80% to 90% and symptoms in 84% to 90% of patients. [11][12][13][14][15][16][17] Therefore, TASH may be an effective alternative to surgery.…”
mentioning
confidence: 99%
“…Since the early 1960s, surgery (ie, ventricular septal myectomy) has been the primary treatment option for drug-refractory, severely symptomatic patients with the obstructive form of HCM. [5][6][7][8][9][10][11][12][13][14] See p 2033…”
mentioning
confidence: 99%